2021
DOI: 10.2147/ijgm.s330142
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Noninvasive Assessment of Arterial Stiffness with 10-Year Atherosclerotic Cardiovascular Disease (ASCVD) Risk in a General Middle-Age and Elderly Population

Abstract: As a powerful indicator of arterial stiffening, the brachial-ankle pulse wave velocity (baPWV) has been extensively validated for predicting cardiovascular events. However, whether and how the brachial-ankle pulse wave velocity (baPWV) is correlated with the 10-year atherosclerotic cardiovascular disease (ASCVD) risk is unclear. This study aimed to investigate the association between baPWV and 10-year ASCVD risk in Chinese population. Methods: A total of 1768 subjects were enrolled from Shanghai, China. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“… 31 Similarly, as a powerful indicator of arteriosclerosis, 32 baPWV has been proved to be closely related to the 10-year risk of atherosclerotic cardiovascular disease (ASCVD) in the middle-aged and elderly population. 33 Through multiple stepwise linear regression analysis, this study found that hemorrhagic pentosidine was significantly correlated with these two indicators. We speculated that the increase of serum pentosidine caused vascular inflammation and oxidative stress, affected the cross-linking of angioplasty protein and collagen, resulting in vascular sclerosis, and then caused cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 79%
“… 31 Similarly, as a powerful indicator of arteriosclerosis, 32 baPWV has been proved to be closely related to the 10-year risk of atherosclerotic cardiovascular disease (ASCVD) in the middle-aged and elderly population. 33 Through multiple stepwise linear regression analysis, this study found that hemorrhagic pentosidine was significantly correlated with these two indicators. We speculated that the increase of serum pentosidine caused vascular inflammation and oxidative stress, affected the cross-linking of angioplasty protein and collagen, resulting in vascular sclerosis, and then caused cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study involving 3876 older people in Shanghai, baPWV was closely related to all‐cause death, cardiovascular death, and stroke events during a median follow‐up of 5.9 years 29 . Another study showed that an increase in baPWV correlates strongly with the 10‐year ASCVD risk, as calculated by the Pooled Cohort Equations model, in general middle‐aged and older Chinese populations 30 31 .…”
Section: Discussionmentioning
confidence: 94%
“…29 Another study showed that an increase in baPWV correlates strongly with the 10-year ASCVD risk, as calculated by the Pooled Cohort Equations model, in general middleaged and older Chinese populations. 30 A meta-analysis also found that, similar to cfPWV, baPWV is independently associated with an increased risk of cardiovascular events, cardiovascular mortality, and all-cause mortality in patients with ASCVD in East Asia. 31 A previous study suggested that geographic region is an important factor affecting the ASCVD risk 3 ; however, large-sample and long-term follow-up studies in the population of northern China are lacking.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations